I ran into this problem on homework and i cant figure it out. If anyone could walk me through it step by step it would be greatly appreciated. -2[(4p+1)-(3p-1)] = 5(3-p)-9
Follow Math Help Forum on Facebook and Google+
Originally Posted by Meier I ran into this problem on homework and i cant figure it out. If anyone could walk me through it step by step it would be greatly appreciated. -2[(4p+1)-(3p-1)] = 5(3-p)-9 Work from the innermost brackets and go outwards: $\displaystyle -2(4p+1-3p+1) = 15-5p-9$ $\displaystyle -2(p+2) + 5p + 9 - 15 = 0$
View Tag Cloud